2017 13th European Dependable Computing Conference (EDCC) 2017
DOI: 10.1109/edcc.2017.27
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-Based Vulnerability Assessment Applied to Operating Systems

Abstract: Abstract-Organizations face the issue of how to best allocate their security resources. Thus, they need an accurate method for assessing how many new vulnerabilities will be reported for the operating systems (OSs) they use in a given time period. Our approach consists of clustering vulnerabilities by leveraging the text information within vulnerability records, and then simulating the mean value function of vulnerabilities by relaxing the monotonic intensity function assumption, which is prevalent among the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Movahedi et al [29] developed nine common vulnerability discovery models (VDMs) which were compared with a nonlinear neural network model (NNM) over a prediction period of three years. The common VDMs are the NHPP power-law gamma-based VDM, Weibull-based VDM, AML VDM, normalbased VDM, rescorla exponential (RE), rescorla quadratic (RQ), younis folded (YF) and linear model (LM).…”
Section: Related Researchmentioning
confidence: 99%
“…Movahedi et al [29] developed nine common vulnerability discovery models (VDMs) which were compared with a nonlinear neural network model (NNM) over a prediction period of three years. The common VDMs are the NHPP power-law gamma-based VDM, Weibull-based VDM, AML VDM, normalbased VDM, rescorla exponential (RE), rescorla quadratic (RQ), younis folded (YF) and linear model (LM).…”
Section: Related Researchmentioning
confidence: 99%
“…The dataset used in this paper was collected from the National Vulnerability Database (NVD) maintained by NIST, and collected using the same approach followed by [24]. We leveraged the vulnerability CVE IDs to compare the reporting date of each vulnerability in NVD with the dates in other public repositories on vulnerabilities 1 .…”
Section: Datasetmentioning
confidence: 99%
“…Allodi [27] showed that the discovered vulnerabilities may follow a Power-law distribution. The model used in this paper was applied on vulnerability data as a VDM in [24] [18]. The main assumption of this model [28].…”
Section: Gamma-based Vdm [8]mentioning
confidence: 99%